A A Systematic Review: Factors Contributing to Burnout Among Nurses in Emergency Departments - Muslim, Fariz Jauhar (CV. AFDIFAL MAJU BERKAH, 2025)
The Emergency Department (ED) plays a vital role in hospitals, requiring nurses to act swiftly and accurately under pressure. However, high workloads and psychological stress make ED nurses particularly vulnerable to burnout syndrome. Burnout can lead to decreased service quality, impaired concentration, reduced empathy, and increased risk of medical errors. This study aims to identify factors influencing burnout among ED nurses through a systematic review using the PICOS framework (Population, Intervention, Comparison, Outcomes, Study Design). A literature search was conducted from May to June 2025 across four databases—Google Scholar, PubMed, DOAJ, and Science Direct—using keywords in both Indonesian and English. Out of 4,034 articles, 13 met the inclusion criteria. The review identified several contributing factors, including workload, employment duration, age, gender, coping strategies, education level, job demands, emotional intelligence, role conflict, social support, work environment, adaptability, patient case types, health status, self-care, staff shortages, job repetition, and compensation. Among these, workload and employment duration emerged as the most significant contributors. To reduce burnout, it is crucial to manage nurse workloads, align tasks with expertise, and implement flexible scheduling and leave policies. These measures can help preserve the well-being and performance of ED nurses in their critical roles